Finite Element Analysis of Reinforced Concrete Deep Beams - Ahmed, Muhammed M.; Hasan, Sarkawt A. (Sulaimani Journal for Pure and Applied Sciences, 2001)
The nonlinear analysis of reinforced concrete deep beams using finite element method is presented here. The nonlinearity included the nonlinear behavior, anisotropy under biaxial state of stress, cracking and crushing of concrete. The post cracking shear transfer in concrete by aggregate interlock and yielding of reinforcement are also considered in the analysis. A quadrilateral eight-noded isoparametric elements were used to represent concrete materials, while bar elements perfectly connected to the concrete nodes were used to represent the steel. Validity of the proposed model was checked by analysis of three reinforced concrete deep beams. The results showed good agreement with experimental ones. Deep beams with openings of different sizes and locations were also analyzed. The results showed that proposed model can represent effects of the openings on behavior of deep beams including ultimate load capacity, crack propagation, stress and strain 4